212 - QUALITY OF GAIT IN ELDERLY WOMEN: AN AQUATIC PHYSIOTHERAPY PROPOSAL (Fiep Bulletin - online, 2011)
Currently, the population has experienced a growing aging process, which is characterized by several changes occurring in the body, causing gradual reduction of the efficiency of the locomotor system, decreasing functional capacity, and independence of this population. The aquatic physiotherapy has been used as a physiotherapeutic resource to prevent, retain, retard, get better or treat physical dysfunctions specifics of aging, because the aquatic environment is considered safe and effective in the rehabilitation of the elderly. The aim of this study was to evaluate the performance of the gait after the intervention of aquatic physiotherapy in elderly women. The sample consisted of 10 elderly, with an average age of 64 years. The gait of the subjects was evaluated at two different times, before and after the aquatic physiotherapy intervention, and the Dynamic Gait Index was used as an evaluation protocol. The program of aquatic physiotherapy included the use of kinesthetic exercises adapted to the water. After five weeks of aquatic physiotherapy intervention, there has been a significant improvement (p=0,00) in the scores average of the Dynamic Gait Index, which indicates an improvement in the quality of gait of elderly people. Thus, this study found that water physiotherapy, through a kinesthetic exercise program adapted to the water, has a positive effect on the quality of gait in the elderly population.
Keywords: Elderly women; Gait; Aquatic physiotherapy